Cognitive assessment and intervention in occupational therapy for Thai older adults with neurocognitive disorders - Chaiwong, Pachpilai; Sungkarat, Somporn; Rattakorn, Phuanjai; Munkhetvit, Peeraya (Journal of Associated Medical Sciences, 2022)
Background: Occupational therapists (OTs) have a significant role in maintaining clients' well-being. Understanding the current occupational therapy (OT) practice for the elderly with neurocognitive disorders (NCDs) brings effective service. Objectives: This study aimed to explore current OT practice for cognitive assessment and intervention for the elderly with NCDs in Thailand. Materials and methods: This study explored OT practices via questionnaire. Questionnaires were distributed to one hundred and ninety-one OTs throughout Thailand. Results: One hundred and fifty-two occupational therapists (79.87%) responded to the survey. Most worked full-time (94.08%), and 74.34% worked at general hospitals. Participants were more likely to employ standardized cognitive tests (45.33%) than non-standardized assessments (38.00%). Typical standardized tests were screening tests rather than comprehensive tests. The most reported cognitive problem was basic cognition (77.63% to 98.08%). The main cognitive intervention focused on basic cognition (80.92% to 94.74%). Typical interventions were caregiver education (83.89%), physical activity (73.15%), and perceptual retaining (68.46%). Challenges to OT intervention were therapists had poor evaluation skills, unclear intervention guidelines, and an insufficient number of therapists. Conclusion: OTs should participate in further education and develop a guideline and appropriate comprehensive cognitive assessment tools.